TRANSLATION PECULIARITIES OF ALLUSIVE TITLES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The aim of the paper is to study translation peculiarities of allusion, specifically allusive titles in J.D. Salinger’s “The Catcher in the Rye”. The article highlights the main strategies that were implemented by the translators. Two versions of translation are discussed in the paper. Comparative and contrastive methods have been conducted to reveal translation differences between direct and indirect translations.